Engineering strategies for enhancement of bio-hydrogen production by phototrophic bacterium Rhodopseudomonas palustris - Du Toit, Jan-Pierre (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.